Salinomycin mediated therapeutic targeting of circulating stem like cell population in oral cancer. Issue 21 (5th December 2022) - Patel, Shanaya; Patel, Aditi; Nair, Aishwarya; Shah, Kavan; Shah, Kanisha; Tanavde, Vivek; Rawal, Rakesh
Abstract: CD44+ circulating tumor stem cells (CTSCs) have been significantly associated with aggressiveness, resistance and poor prognosis of oral cancer patients. Thus, targeted elimination of these CTSCs could be a new conceptual framework for enhancing the therapeutic outcome of patients. Docking of potential investigational molecules and simulation results identified Salinomycin as a potential lead compound that could effectively inhibit CD44 receptor. To assess the cytotoxic effect, immuno-magnetically sorted circulatory CD44+ cells were subjected to increasing concentrations of 5FU, Cisplatin and Salinomycin. Salinomycin demonstrated significant cytotoxic effect towards the CD44+ subpopulation in a dose and time dependent manner. Further the effect of these compounds was investigated on apoptosis, cell cycle, signaling pathways and gene expression profiles using Muse TM flow cytometer and Real-Time PCR. It was observed that mRNA expression patterns of CD44v6, Nanog, AKT1, CDKN2A and β-catenin of Salinomycin treated CD44+ cells. Moreover, Salinomycin significantly induced programmed cell death by inducing G2/M cell cycle arrest and inhibiting MAPK/PI3K pathways in this chemo-resistant population. Thus, this study demonstrated the potential of Salinomycin to target the chemo-resistant circulating CD44 population by attenuating its proliferation and survival. Communicated by Ramaswamy H. Sarma